A STUDY ON THE RELATION BETWEEN GENERAL CYNISM AND COLLEGE ALIENATION PERCEPTION OF STUDENTS - Tevfik UZUN (Fırat University, 2019)
This study focuses on the relation between the students’ perception of general cynism and college alienation. Relational screening model is chosen to conduct the study. Sample of the study covers 537 vocational school students from a state university. In order to determine the general cynism level of the students, General Cynism Scale developed by Wrightsman (1992) is used. College Alienation Survey developed by Burbach (1972) is also used to have an idea of the college alienation level of the students. Percentage, frequency, median, standard deviation, correlation analysis, basic and multi linear regression, for non-parametric tests independent t-test, and for independent samples one-way variance analysis (ANOVA) tests are used to calculate the gathered data. The findings are as follows: general cynism perception of students is found out to be medium-level with the majority of I Am Not Sure option. It is found out that students’ general cynism perception is not affected by gender, age, department, peers and relations with them while the finding is meaningful in terms of financial situation and interaction with lecturers. College alienation level is also found medium-level with the answer I Partially Agree. Sample group’s alienation perception does not differ meaningfully in terms of gender and age. However, difference is found in college alienation perception in terms of class, department, financial situation, interaction with classmates and lecturers. When it comes to the relation between the two; it is also turned out to be a positive correlation at intermediate level. General cynism perception of the students predicts the perception of college alienation meaningfully and positively.